Epidemiology of Sports-Related Concussion in NCAA Athletes From 2009-2010 to 2013-2014: Incidence, Recurrence, and Mechanisms. (November 2015) - Zuckerman, Scott L.; Kerr, Zachary Y.; Yengo-Kahn, Aaron; Wasserman, Erin; Covassin, Tracey; Solomon, Gary S.
Background: The epidemiology of sports-related concussion (SRC) among student-athletes has been extensively researched. However, recent data at the collegiate level are limited. Purpose: To describe the epidemiology of SRC in 25 National Collegiate Athletic Association (NCAA) sports. Study Design: Descriptive epidemiology study. Methods: SRC data from the NCAA Injury Surveillance Program during the 2009-2010 to 2013-2014 academic years were analyzed. Concussion injury rates, rate ratios (RRs), and injury proportion ratios were reported with 95% CIs. National estimates were also calculated to examine linear trends across time. Results: During the study period, 1670 SRCs were reported, representing a national estimate of 10, 560 SRCs reported annually. Among the 25 sports, the overall concussion rate was 4.47 per 10, 000 athlete-exposures (AEs) (95% CI, 4.25-4.68). Overall, more SRCs occurred in competitions (53.2%). The competition rate (12.81 per 10, 000 AEs) was larger than the practice rate (2.57 per 10, 000 AEs) (competition vs practice, RR = 4.99; 95% CI, 4.53-5.49). Of all SRCs, 9.0% were recurrent. Most SRCs occurred from player contact (68.0%). The largest concussion rates were in men's wrestling (10.92 per 10, 000 AEs; 95% CI, 8.62-13.23), men's ice hockey (7.91 per 10, 000 AEs; 95% CI, 6.87-8.95), women's ice hockey (7.50 per 10, 000 AEs; 95% CI, 5.91-9.10), and men's football (6.71 per 10, 000 AEs; 95% CI, 6.17-7.24). However, men's football had the largest annual estimate of reported SRCs (n = 3417), followed by women's soccer (n = 1113) and women's basketball (n = 998). Among all SRCs, a linear trend did not exist in national estimates across time ( P = .17). However, increases were found within specific sports, such as men's football, women's ice hockey, and men's lacrosse. Conclusion: The estimated number of nationally reported SRCs has increased within specific sports. However, it is unknown whether these increases are attributable to increased reporting or frequency of concussions. Many sports report more SRCs in practice than in competition, although competition rates are higher. Men's wrestling and men's and women's ice hockey have the highest reported concussion rates. Men's football had the highest annual national estimate of reported SRCs, although the annual participation count was also the highest. Future research should continue to longitudinally examine SRC incidence while considering differences by sex, division, and level of competition.